Analisis Semiotika Lirik Lagu Berjudul “Online” - Dewi Kartika Sari (Cakrawala Jurnal Penelitian Sosial, 2017)
This paper is about to review the lyrics of songs that mark the emergence of information society in Indonesia. The observed song lyrics are the lyrics of a song titled “Online” popularized by Saykoji Artist. The theory used is Saussure's semiotics. The research approach used in this analysis is qualitative approach with descriptive research type. The results of this study indicate that the song titled Online describes the characteristics of the information age society at the time.